Type I posterior glottic stenosis: an endoscopic approach - Azevedo, Sara R.; Pinto, Ana N.; Coutinho, Miguel B.; Meireles, Luís (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Type I posterior glottic stenosis (PGS) is a rare and challenging entity that is defined by the presence of a posterior glottic scar band separate from interarytenoid mucosa. This case reports a child who developed PGS-I secondary to prolonged intubation submitted to an endoscopic approach. 11-year-old boy presented with a 4 years complaint of stridor triggered by physical efforts and sleep. He had an history of mechanical ventilation with entubation for a thirty day period. On indirect laryngoscopy it was observed a complete adduction and incomplete abduction of vocal folds. He underwent a diagnostic laryngotracheoscopy, where it was possible to observe and confirm the diagonis of a PGS type I. A suspension microlaryngoscopy was performed and the interarytenoid band tissue was sectioned and dilatation of this area with a balloon was done. Endotracheal intubation is the primary cause of PGS in children. Different surgical interventions have been described, from open to endoscopic techniques. A careful preoperative assessment helps achieve better outcomes.